Effect of loading rate on fracture mechanics of NiTi SMA - Mutlu, Fatma; Anlaş, Günay; Moumni, Ziad (International journal of fracture, 2020)
Superelastic NiTi shape memory alloy is characterized by phase transformation under loading. In this work, the effect of loading rate on fracture mechanics of NiTi is investigated. First, to characterize the behavior of the material, tensile experiments are conducted on dog-bone specimens at different quasi-static-range loading rates and the transformation stresses–strains are calculated. An increase in forward transformation stresses–strains, and a decrease in the reverse transformation stresses–strains with increasing loading rate is observed. Surface mean temperature is measured using a thermal camera, and an increase in temperature difference is observed with increasing loading rate. Displacement field and strain maps are obtained simultaneously using Digital Image Correlation (DIC). The strain maps show strain localizations that change with increasing loading rate. At higher loading rates, localized strain bands increase in number. Fracture experiments are then conducted under Mode I loading on plane stress Compact Tension (CT) specimens, and for further confirmation of the behavior, Finite Element Analysis (FEA) is used with a user defined subroutine to account for thermomechanical coupling. Crack mouth opening displacements (CMODs) are measured and an increase with increasing loading rate is observed. Stress Intensity Factors (SIFs) are calculated using ASTM E399 equations, the displacement data obtained from DIC, and FEA. In all cases, stress intensity factors show an increasing-decreasing trend with increasing loading rate. Results are summarized in a figure to show the trend. Austenite to martensite transformation region sizes around the crack tip are evaluated experimentally, analytically and computationally, and are found to be decreasing with increasing loading rate as well. An interesting but coherent behavior in change of fracture parameters with increasing loading rate is obtained. This study is expected to stimulate new discussions on the subject.